2010
DOI: 10.1038/cr.2010.54
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR) gene results in albino, dwarf and defects in trichome initiation and stomata closure in Arabidopsis

Abstract: 1-Deoxy-d-xylulose-5-phosphate reductoisomerase (DXR) is an important enzyme involved in the 2-C-methyl-d-erythritol-4-phosphate (MEP) pathway which provides the basic five-carbon units for isoprenoid biosynthesis. To investigate the role of the MEP pathway in plant development and metabolism, we carried out detailed analyses on a dxr mutant (GK_215C01) and two DXR transgenic co-suppression lines, OX-DXR-L2 and OX-DXR-L7. We found that the dxr mutant was albino and dwarf. It never bolted, had significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 73 publications
3
49
0
1
Order By: Relevance
“…OeDXS OeDXR and OeHMBPPR had the strongest differential expression in accordance with their key role in the MEP pathway, which has been proposed in other plant species [40-42]. In particular, our results showed that OeDXS, which is involved in the first step of the MEP pathway, was exclusively expressed in the first developmental stage (45 DAF) in both cultivars.…”
Section: Resultssupporting
confidence: 86%
“…OeDXS OeDXR and OeHMBPPR had the strongest differential expression in accordance with their key role in the MEP pathway, which has been proposed in other plant species [40-42]. In particular, our results showed that OeDXS, which is involved in the first step of the MEP pathway, was exclusively expressed in the first developmental stage (45 DAF) in both cultivars.…”
Section: Resultssupporting
confidence: 86%
“…6 and Table 2). Our data indicate that CDS_CCI2 has an important role in secondary metabolism processes, which is in accordance with study on disruption of the 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR) gene results in albino, dwarf and defects in trichome initiation and stomata closure in Arabidopsis (Xing et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Chl and carotenoids were extracted from the aboveground parts of 40-day-old Arabidopsis, as described previously [33]. Absorbance ( A ) of the final solution at 663, 647 and 470 nm was measured and the concentrations of Chl a (Ca), Chl b (Cb) and carotenoids (Cc) were calculated as follows [34]: …”
Section: Methodsmentioning
confidence: 99%